2022
DOI: 10.3390/genes13020233
|View full text |Cite
|
Sign up to set email alerts
|

A Gain-of-Function Mutation on BCKDK Gene and Its Possible Pathogenic Role in Branched-Chain Amino Acid Metabolism

Abstract: BCKDK is an important key regulator of branched-chain ketoacid dehydrogenase complex activity by phosphorylating and so inactivating branched-chain ketoacid dehydrogenases, the rate-limiting enzyme of the branched-chain amino acid metabolism. We identified, by whole exome-sequencing analysis, the p.His162Gln variant of the BCKDK gene in a neonate, picked up by newborn screening, with a biochemical phenotype of a mild form of maple syrup urine disease (MSUD). The same biochemical and genetic picture was present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Nowadays, there is a great progress in the detection of amino acids at very low concentrations in complex matrixes, including liquid chromatography-mass spectrometry (LC-MS) and capillary electrophoresis-mass spectrometry (CE-MS) (6,8,9). Liquid chromatography and tandem mass spectrometry appear to be the major methods for detecting plasma BCAAs nowadays (10)(11)(12)(13).…”
Section: Detection Methods Of Branched-chain Amino Acids and Branched...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, there is a great progress in the detection of amino acids at very low concentrations in complex matrixes, including liquid chromatography-mass spectrometry (LC-MS) and capillary electrophoresis-mass spectrometry (CE-MS) (6,8,9). Liquid chromatography and tandem mass spectrometry appear to be the major methods for detecting plasma BCAAs nowadays (10)(11)(12)(13).…”
Section: Detection Methods Of Branched-chain Amino Acids and Branched...mentioning
confidence: 99%
“…BCKAs especially the KIC allosterically regulate BCKDK. If the BCKAs are at high concentration, BCKAs will inhibit the activity of BCKDK, preventing BCAAs from running out when they are at low concentration ( 6 ). However, BCKDK also seems to be regulated by the BCKDH complex, the details of the mechanism need to be studied ( 6 ).…”
Section: Branched-chain Amino Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a newborn with a biochemical phenotype suggestive of MSUD with a heterozygous gain-of-function BCKDK variant was reported. The asymptomatic father and grandfather also carried the same variant (Maguolo et al, 2022). In addition, Oyarzabal et al discovered a homozygous truncating variant in PPM1K in a 21-year-old woman with mild MSUD (Oyarzabal et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…This disease is characterized by the accumulation of BCKA and BCAA in plasma and urine, which has severe clinical consequences, including often fatal acidosis, neurological derangement, and developmental delay ( 20 ). Recently, a gain-of-function BCKDK variant with a single mutation at its physiological ligand-binding site was reported to be associated with a mild form of maple syrup urine disease ( 21 ). Recent metabolomics studies have further reported that elevated blood BCAA concentration is associated with insulin resistance and nonalcoholic fatty liver disease ( 22 , 23 , 24 , 25 ).…”
mentioning
confidence: 99%